Unravelling the Dynamic Capture of Antibiotics by Conjugated Microporous Polymers. Issue 27 (22nd July 2019) - Li, Li; Ge, Lei; Chen, Shiqian; Yuan, Hao; Min, Yuxiang; Xu, Lai
Abstract: The encapsulation of antibiotic molecules in conjugated microporous polymers is investigated by using the density functional theory (DFT) method and molecular dynamics (MD) simulations. We find that guest molecules are firstly wrapped around the edges of the polymer nanopores, and as the number of guest molecules increases, they begin to move from the edge to the center of the pore to further stabilize the complex. We discover a parallel sandwich‐type encapsulation model, it is the most stable configuration in which the guest molecules reside in the host framework, and the pore size of the host framework also changes with the entry of guest molecules. The significantly strong adsorption of antibiotics to CMP can be ascribed to charge transfer between the electron‐rich groups and electron‐withdrawing groups. These detailed insights would promote the design of new conjugated microporous polymers for the adsorption of antibiotics, which may provide new opportunities for the treatment of water pollution caused by antibiotics. Abstract : Conjugated microporous polymer (CMP) is effective for capture of antibiotics. The parallel sandwich wrapping model and the flexibility of host polymer were discussed. Molecular dynamics (MD) simulations indicate that all original encapsulations favor a parallel sandwich encapsulation. The binding energies of host‐guest systems are −129.9, −174.7 and −128.6 kcal/mol respectively, which proves that the parallel sandwich wrapping model is kinetically and thermodynamically stable. Systematic mechanism studies are analysed to describe the guest encapsulation behavior of CMP.